The Memory of Female Characters in the Novel Teenage Virgins in the Grip of the Military by Pramoedya Ananta Toer: a Review of Literary Memory - Sinta Ariska; Suantoko Suantoko; Mansur Mansur (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2022)
The Indonesian state stands by leaving a long history behind. Indonesian historical records show that the Indonesian state was colonized or occupied by the Japanese for 3.5 years, starting from March 8, 1942 and ending on Independence Day, August 17, 1945. Of course, that specific period left its mark in the shape of indelible memories on the collective minds of the colonized population. The social reality applied by the Japanese, as recorded in the memory of the indigenous population is far from positive and can even be classified as difficult to accept. One of these dark events was recorded in Pramoedya Ananta Toer's novel TeenageVirgins in the Grip of the Military.This study aims to describe the memory of female characters. Cognitive Psychology has been used as an approach in this study. Cognitive Psychology is regarded as a part of psychology that focuses on the study of perception, memory, and decision-making. This is a challenging subject to study because it deals with behavior. The data analysis techniques make use of Miles and Huberman who specialize in workflows: data collection, reduction, presentation, and data verification. The results show that the female character recalled in her memory that the soldiers from Nippon had raped a local female student. This brings about memory transmission and has traumatic consequences for women who have been 'grabbed'. Women are sexually assaulted. The incident made Buru Island women marginalized. The women of Buru Island never had the opportunity to learn as had been promised. Such treatment triggers a nightmarish and traumatic memory.